Development of a Web-Based Application to Analyze the Comments of the Genshin Impact Virtual Community Official - Fauzan, Harist Asyari; Kurniawan, Rahadian; Paputungan , Irving Vitra (Syntax Literate, 2025)
Online games are now evolving into interactive social spaces that give rise to dynamic virtual communities. One of the communities that is quite well-known in Indonesia is Genshin Impact Indonesia Official, which is often the talk of the town on social media. The problem in this study focuses on how the involvement of players in the community has both positive and negative impacts. The purpose of this research is to analyze the comments of community members to recognize the forms of expression and categories of impacts caused. The research data was collected from 100 random comments on the Genshin Impact Player Restlessness Facebook group during the period of July 8–12, 2025. The method used is Directed Content Analysis (DCA) with the classification framework of Belfiore and Bennett, which includes 12 categories of cultural participation impacts. In addition, the analysis is carried out based on the classification of sentiment (positive, negative, neutral). The findings of this study show that most of the comments are positive, especially in the aspects of Personal Well-being, Appreciation of Game Design, and Personal Development. While negative comments are generally related to the issue of Social Stratification and the pressures due to game mechanics. In addition, the research also resulted in a web-based application for the automation of data classification and visualization, which has been proven to facilitate the analysis process.